1982
DOI: 10.1902/jop.1982.53.9.557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Short‐Term Administration of Minocycline HCl on Gingival Inflammation and Subgingival Microflora,

Abstract: The purpose of this investigation was to determine the efficacy of minocycline hydrochloride in the management of subgingival microorganisms and periodontal disease. In a double‐blind, split‐mouth study, minocycline or placebo was administered systemically for 7 days to 26 adults with moderate‐to‐severe periodontitis. Four study groups were examined: (i) minocycline‐scaled, (ii) minocycline‐unscaled, (iii) placebo‐scaled, and (iv) placebo‐unscaled. The minocycline‐scaled group responded most favorably, with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 19 publications
3
32
0
Order By: Relevance
“…The latter finding suggests that there is no significant difference in PD reduction between mechanical treatment alone and mechanical treatment combined with doxycycline. These findings are consistent with the findings of several previous studies in which no significant difference could be found between mechanical treatment combined with tetracycline or minocycline and mechanical treatment alone (10,11,16). However, contrary findings have also been reported.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The latter finding suggests that there is no significant difference in PD reduction between mechanical treatment alone and mechanical treatment combined with doxycycline. These findings are consistent with the findings of several previous studies in which no significant difference could be found between mechanical treatment combined with tetracycline or minocycline and mechanical treatment alone (10,11,16). However, contrary findings have also been reported.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies on clinical effects of both systemic and local tetracyclines have been performed. In some of these studies, tetracyclines made no statistically significant difference on probing depths and clinical attachment levels (10,11,(14)(15)(16)(17)(18)(19) while in others successful clinical results were obtained by tetracycline and minocycline treatments (20)(21)(22)(23)(24)(25)(26)(27)(28). These studies evaluated only systemic or local antibiotic treatments with or without mechanical periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, extensive studies have been conducted with metranidazole and tetracyclines [7,[9][10][11][12]22,23]. Due to their high concentration in gingival crevicular fluid, their ability to bind to bone and inhibit tissue collagenase, tetracyclines are the most recommended group of antibiotics for treatment of periodontal disease [13,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Systemically administered antibacterial agents are being tried with increasing frequency for the clinical management of periodontal problems [7,[9][10][11][12]. Tetracyclines are one group of antibiotics that have been used widely in the treatment of periodontal disease [7,9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although systemic administration of antibiotics has been shown to be of value in the control of periodontal diseases, these treatments are mainly beneficial as adjuvants to mechanical debridement (Ciancio et al, 1982;Lindhe et al, 1983;Lundstrom et al, 1984). Anti-bacterial activity alone cannot predict the efficacy of a drug as an anti-plaque agent (Gjermo et al, 1970).…”
Section: Discussionmentioning
confidence: 99%